Lithuanian Discourse Markers in Parallel Corpus for Teaching Translation Awareness - Valūnaitė Oleškevičienė, Giedrė; Karaciejūtė, Vitalija; Gulbinskienė, Dalia; Annamalai, Nagaletchimee (Pedagogika, 2023)
The contrastive analysis of discourse markers in Lithuanian and English provides data on the functions of discourse markers to language teachers and translators. The study reveals that there is a tentative tendency for translators to rarely choose to run an explicit discourse marker and leave it only in the implied translation. It is essential that philology students are taught in detail about discourse markers, and TED-MBD is an excellent medium for teaching text coherence.